Komparasi Implementasi Konsep Smart City di Kota dan Kabupaten (Studi Kasus: Kota Surakarta dan Kabupaten Sukoharjo) - Cahyadani, Lestyanto; Djunaedi, Achmad (Institut Teknologi Nasional Yogyakarta, 2024)
Hierarchically, City and Regency are equal in the government system of Indonesia. However, there are differences in characteristics between them. The difference also allow defferent approaches in implementing a policy, including smart city. Purpose of this research is to identify the correlation between that difference characteristics and the implementation of smart city. This research uses case study method and uses data sources such as documents, interview, and observation. That three data sources were analyzed using triangulation method to validate the results of analysis process. The result of this research shows that there are correlations between the implementation of smart city and the issues in the City and the Regency. Application of the smart city concept in Surakarta City is mostly influenced by the issues of urban area, such as dense population, lack of resources, urban communities, and high intensity of transportation. Meanwhile, in Sukoharjo Regency, implementation of smart city is influenced by issue of rural and peri-urban areas e.g lots of open space, abundant natural resources, low population density, rural communities, facilites gap, and indutrial waste.